Tibial cortex transverse transport corticotomy: A case series on a novel approach to limb salvage in the setting of peripheral vascular disease - Matthew A. Peter, DPM; Shane Sato, DPM; Michael H. Theodoulou, DPM (Foot & Ankle Surgery: Techniques, Reports & Cases)
Lower extremity wounds complicated by chronic limb threatening ischemia (CLTI), especially in the setting of diabetes mellitus, present significant challenges, often leading to delayed healing and increased risk of amputation with limited treatment modalities. The tibial transverse transport corticotomy technique is a novel approach and a promising intervention for severe diabetic foot ulcers (DFU). Three cases illustrate successful outcomes with the described procedure in which healing was challenged through conventional treatment methods. The tibial transverse transport corticotomy offers hope as an effective treatment modality for cases of severe diabetic foot ulcer, complicated by CLTI, to improve wound healing and limb salvage in the lower extremity.